Nano-optofluidics for single molecule detection and sorting - Yang, Y. (2013)
This paper reports a nano-optofluidic device using evanescent wave sensing for single molecule detection and sorting based on hydrodynamic focusing and total internal reflection (TIR). Nano-sized samples in liquid can be measured and counted even their size is smaller than the diffraction limit. We demonstrated 200-nm nanoparticle detecting which is beyond the diffraction limit. As compared to the conventional TIR microscopy, the nano-optofluidic device can measure and count all samples in real time. It has wide range applications in the single molecule detection, imaging and counting.